Risk Analysis Using the Enterprise Risk Management (ERM) Method in the Implementation of Standard Inpatient Class at Sultan Agung Islamic Hospital - Ayu Sekar Melati; Sutopo Patria Jati; Septo Pawelas Arso (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
The implementation of the Standardized Inpatient Class (KRIS) is a national strategic policy aimed at improving equity and quality of care for participants of Indonesia’s National Health Insurance (JKN). However, the transition toward standardized inpatient facilities may generate complex operational, patient safety, and financial risks that extend beyond technical compliance. An Enterprise Risk Management (ERM) approach is therefore required to comprehensively identify and manage these cross-domain risks, which have been insufficiently explored in previous KRIS-related studies. This study aims to identify the risk profile and formulate mitigation strategies for KRIS implementation using an ERM framework. A mixed-methods sequential explanatory design was applied, consisting of a quantitative survey of 30 inpatient unit heads followed by qualitative in-depth interviews and Focus Group Discussions (FGD) with hospital management. Quantitative data were analyzed using descriptive statistics and a 5×5 risk matrix, while qualitative data were analyzed through thematic content analysis. The results identified three highest-priority risks: changes in service flow due to renovation (mean 18.3), reduced bed capacity during the transition period (17.9), and increased cross-infection risk due to crowding in temporary inpatient rooms (17.4). Financial risks, human resource readiness, regulatory uncertainty, and information system limitations were predominantly categorized as moderate to high. Integrated findings emphasize the importance of structured change management, strengthened infection prevention, comprehensive financial planning, and improved staff readiness supported by adequate information systems. In conclusion, KRIS implementation requires a systematic and integrated risk management approach to ensure effective, safe, and sustainable hospital service transformation. Keywords: Enterprise Risk Management, KRIS Implementation, Hospital Risk Assessment, Patient Safety, Health Policy Transition.